Medžida Selmanović (1937-2009) and her contribution to Ottoman studies - on the 15th anniversary of her death - Bavčić, Mubera (Historical Thought, 2024)
On the occasion of the fifteenth anniversary of the death of Medžida Selmanović, this paper presents the biographical data, as well as information about her thirtysix years of work at the Oriental Institute as an archivist, where she held the professional title of an Archivist-Turkologist and Senior Archivist, then of ResearcherOttomanist, and finally of Researcher-Associate-Ottomanist, which she kept until her retirement in 2002. In addition to her regular duties in the Oriental Institute archives, Medžida Selmanović devoted most of her working life to the scholarly processing of defters and translation of Ottoman historical sources. Apart from works on historical themes, she published several significant works in the field of diplomatics and palaeography, as well as Islamic art and miniatures. The attached bibliography of this author’s publications provides a more complete insight into her research.